Gastronomic tourism in Uzbekistan (on the example of Samarkand). - Xakberdievna, Sidikova Mastura (The journal of contemporary issues in business and government, 2021)
This journal has analyzed gastronomic tourism in Uzbekistan. Moreover, author has analyzed gastronomic tourism industry both from theoretical and methodological points in the examples of Samarkand. The way of tourism development through gastronomic tourism has been pinpointed while making accents on outcomes and shortcomings as the whole.